2018
DOI: 10.3390/rs10060834
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton Size Structure in Association with Mesoscale Eddies off Central-Southern Chile: The Satellite Application of a Phytoplankton Size-Class Model

Abstract: Understanding the influence of mesoscale and submesoscale features on the structure of phytoplankton is a key aspect in the assessment of their influence on marine biogeochemical cycling and cross-shore exchanges of plankton in Eastern Boundary Current Systems (EBCS). In this study, the spatio-temporal evolution of phytoplankton size classes (PSC) in surface waters associated with mesoscale eddies in the EBCS off central-southern Chile was analyzed. Chlorophyll-a (Chl-a) size-fractionated filtration (SFF) data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 87 publications
1
11
0
Order By: Relevance
“…In summer, prevalent southeasterly winds (Figures 11e and 11f) influenced horizontal advection of coastal and ocean currents, leading to a positive SLA in the central YS (Cai et al, 2015;Qiao, 2005). Previous studies showed that positive SLA was usually accompanied with a decrease in chlorophyll-a concentration and higher proportion of smaller-sized phytoplankton in the surface layer (Bricaud et al, 2012;Corredor-Acosta et al, 2018), which agreed with the observations in Figure 11c and confirmed the positive correlations between SLA and percentages of nanoplankton and picoplankton (Table 2). Moreover, due to the strong solar heating and weak wind forcing, shallow MLD took place in summer (Figure 11d), indicating the existence of a strong thermocline between the shallow mixed surface layer and deeper colder water (Fu et al, 2018).…”
Section: Central Yellow Seasupporting
confidence: 90%
“…In summer, prevalent southeasterly winds (Figures 11e and 11f) influenced horizontal advection of coastal and ocean currents, leading to a positive SLA in the central YS (Cai et al, 2015;Qiao, 2005). Previous studies showed that positive SLA was usually accompanied with a decrease in chlorophyll-a concentration and higher proportion of smaller-sized phytoplankton in the surface layer (Bricaud et al, 2012;Corredor-Acosta et al, 2018), which agreed with the observations in Figure 11c and confirmed the positive correlations between SLA and percentages of nanoplankton and picoplankton (Table 2). Moreover, due to the strong solar heating and weak wind forcing, shallow MLD took place in summer (Figure 11d), indicating the existence of a strong thermocline between the shallow mixed surface layer and deeper colder water (Fu et al, 2018).…”
Section: Central Yellow Seasupporting
confidence: 90%
“…Indeed, Corredor‐Acosta et al. (2018) revealed that the phytoplankton size structure changes within mesoscale eddies could be affected by variations in nutrient concentrations and/or ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the observed picoplankton-dominated community structure under the mesoscale eddies may likely be a reflection of the combined effects of low nutrient supply and chemical composition (i.e., silicate limitation). Indeed, Corredor-Acosta et al (2018) revealed that the phytoplankton size structure changes within mesoscale eddies could be affected by variations in nutrient concentrations and/ or ratios.…”
Section: Table 2 the Comparison Of Total Chl A Biomass And The Contrimentioning
confidence: 99%
“…The unusual physical dynamics such as tropical cyclone (TC) triggers the biogeochemical properties present in the ocean, which disturbs the distribution and dynamics of phytoplankton (Lin, 2012;Wang & Zhao, 2008). Tropical cyclone passage on the sea causes two significant impacts that are generally encountered, first and foremost is intense wind and later is the sizeable freshwater discharge due to heavy rains near the shore (Corredor-Acosta et al, 2018). Most importantly during TC, the ocean faces fluctuation in the physical properties like cooling of sea surface temperature (SST) caused by vertical mixing of the water column (i.e.…”
Section: Introductionmentioning
confidence: 99%